(untitled) (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
In recent years, the process of learning foreign languages has undergone significant changes. The integration of technology into education has led to the widespread use of online platforms designed specifically to facilitate language acquisition. Among these platforms, Quizlet, Kahoot, and Duolingo have gained immense popularity among students and educators. These online resources offer a flexible and engaging environment, allowing learners to access materials and practice English skills anytime and anywhere.